2016
DOI: 10.1093/nar/gkw908
|View full text |Cite
|
Sign up to set email alerts
|

Guide RNA engineering for versatile Cas9 functionality

Abstract: The Clustered Regularly Interspaced Short Palindromic Repeats system allows a single guide RNA (sgRNA) to direct a protein with combined helicase and nuclease activity to the DNA. Streptococcus pyogenes Cas9 (SpCas9), a CRISPR-associated protein, has revolutionized our ability to probe and edit the human genome in vitro and in vivo. Arguably, the true modularity of the Cas9 platform is conferred through the ease of sgRNA programmability as well as the degree of modifications the sgRNA can tolerate without comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 94 publications
0
54
0
Order By: Relevance
“…For scRNA and SAM, EDLL was attached to dCas9 and VP64 was fused to the MS2 viral coat protein, which binds an RNA aptamer. RNA scaffolds in scRNA and SAM designs contained a second optimized aptamer next to the wild type one, as this double-aptamer design was earlier found to improve binding activity 18 . During the cloning of the gRNA2.0 scaffold employed in the scRNA design, a spontaneous mutation occurred consisting in the insertion of an adenine in the loop of the first aptamer ( Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…For scRNA and SAM, EDLL was attached to dCas9 and VP64 was fused to the MS2 viral coat protein, which binds an RNA aptamer. RNA scaffolds in scRNA and SAM designs contained a second optimized aptamer next to the wild type one, as this double-aptamer design was earlier found to improve binding activity 18 . During the cloning of the gRNA2.0 scaffold employed in the scRNA design, a spontaneous mutation occurred consisting in the insertion of an adenine in the loop of the first aptamer ( Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Less than ten colonies were obtained on the plate, possibly due to the high selection pressure of 5'-FOA and the slow cleavage activity of Cpf1: majority of cells were killed by 5'-FOA before they could be edited by Cpf1. It has been recently discovered that the addition of poly-thymidine to the 3'-end of crRNA could improve the AsCpf1 genome editing efficiency (Xie, Minkenberg et al 2015, Nowak, Lawson et al 2016, Bin Moon, Lee et al 2018. We thus modified the crRNA by adding eight thymidine (T8), which will form a poly-U overhang following the 3'-end of the crRNA.…”
Section: Crispr-cpf1 Mediated In-del Mutations Of Counter-selectable mentioning
confidence: 99%
“…Spatiotemporal control has been achieved by regulation of Cas9 via photoactivation 17 or via tissue-specific promoters 18,19 or microRNAs, 20 which comes with the unwelcome restriction that all gRNAs are subject to the same regulatory scope. Systematic mapping of the structure and sequence properties of functional gRNAs has revealed that Cas9 activity is tolerant to significant modifications the standard gRNA structure, 21,22 facilitiating introduction of auxiliary domains that enable conditional control of gRNA activity via structural changes induced by small-molecules, 23,24 protein-bound RNAs, 25 nucleases, 26 or nuclease-recruiting DNAs. 26 Alternatively, the activity of standard gRNAs has been modulated by antisense RNAs 27 or by photolysis of antisense DNAs incorporating photocleavable groups.…”
Section: Introductionmentioning
confidence: 99%